TURNOVER INTENTION: EFFECT OF LEADERSHIP STYLE AND REWARD - Selvia Rusvita Dewi; Anwar Mansyur (SEAN Institute, 2022)
The purpose of this study was to analyze the effect of transformational leadership style, transactional leadership and rewards on employee turnover intention at PT. Bakti Putra Nusantara. Primary data is used here, which means that the data obtained is the original data from the source through a questionnaire. Employees of the production division of PT. Bakti Putra Nusantara was used as a sample. This sampling was carried out using a non-probability sampling technique with a conditional sampling technique (purposive sampling) and the number of samples was 182 respondents. The research data was then analyzed using multiple linear analysis to test the magnitude of the influence partially or simultaneously the dependent variable on the independent variable. The results showed that transformational leadership, transactional leadership, and reward simultaneously have an influence on turnover intention with an Adjusted R Square value of 0.423. The results of the partial test found that transformational leadership has a significant negative effect on turnover intention. Transactional leadership partially has a significant negative effect on turnover intention. Reward partially has a significant negative effect on turnover intention.